Factography and religious discourse as interconnected elements of artistic whole (on the example of the philosophical-allegorical works of M. Harecki «Lyavonius Zadumekus») - Gubskaya, Olga N. (Journal of the Belarusian State University. Philology, 2020)
I used the narratological analysis for reviewing the philosophical and allegorical work of M. Harecki «Lyavonius Zadumekus». The purpose of the article is to prove that the narratological analysis of the structure of M. Harecki’s text reveals new qualities of the work. The concepts of «real author», «abstract author», «narrator» and «event», «history», «narration» are the tools of narratological analysis. The author emphasizes that this text is the example of an expressive narration, in which religious discourse is clearly manifested against the background of an expressive style, which, in turn, actualizes the archetype of the «repentant». It is argued that the basic facts of human existence and the epoch that are highlighted in the text of M. Harecki turn into specific constructs. Elements of religious discourse and the poetics of expressive writing play a leading role in this process. The discovery and proof of the presence of elements of religious discourse and actualization against this background of the archetype of the «repentant sinner» determines the novelty of this article.